Nickel–Gallium Intermetallic Nanocrystal Catalysts in the Semihydrogenation of Phenylacetylene. Issue 3 (12th February 2014) - Li, Changming; Chen, Yudi; Zhang, Shitong; Zhou, Junyao; Wang, Fei; He, Shan; Wei, Min; Evans, David G.; Duan, Xue
Abstract The chemoselective hydrogenation of alkyne is of great importance in the chemical industry, in which intermetallic compounds (IMCs) have attracted extensive interest as efficient catalysts. Herein, we demonstrate the preparation of several supported Ni–Ga IMCs (Ni3Ga, Ni5Ga3, and NiGa) via a facile in situ reduction of layered double hydroxide (LDH) precursors, which demonstrate significantly improved catalytic activity and selectivity for the selective hydrogenation of phenylacetylene to styrene. The composition and particle size of Ni–Ga IMCs can be tuned by adjusting the Ni/Ga ratio or reduction temperature during the topotactic transformation process of LDHs, and the best catalytic behavior can be obtained over the Ni3Ga IMC with a styrene yield of 87.7 % (particle size=7.2 nm at 40 °C and 0.3 MPa), which is better than that of most of the reported Ni catalysts. The X‐ray absorption fine‐structure characterization and DFT calculations reveal the electron transfer from Ga to Ni and active‐site isolation by Ga in Ni–Ga IMCs, which account for the excellent hydrogenation selectivity. The significantly improved catalytic performance makes Ni–Ga IMC catalysts promising candidates for the selective hydrogenation of alkyne.